2008
DOI: 10.1002/jnr.21846
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes for normalization of real‐time quantitative RT‐PCR data in traumatic brain injury

Abstract: Careful validation of reference genes used for the normalization of real-time RT-PCR data is required to obtain accurate results regarding gene expression. We evaluated the stability of seven commonly used reference genes in the cerebral cortex and hippocampus of rats 3 days following traumatic brain injury (TBI). HPRT, SDHA, and GUSB were found to be the most stable reference genes in the cerebral cortex, whereas B2MG, TBP, and GAPDH were the most stable in the hippocampus. The use of three reference genes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 51 publications
8
47
2
Order By: Relevance
“…Variability of the reference genes expression in different tissues and experimental situations was demonstrated in studies of last years [27][28][29][30][31][32]. We also found in the 21 time winners decrease in functional activity of the genes involved in the processes of intracellular protein transport (Cphn) and glycolysis (Gapdh), presented in all nucleated cells (Hprt), which suggests a profound influence of positive fighting experience on different metabolic and cellular processes in the raphe nuclei of the midbrain.…”
Section: Discussionsupporting
confidence: 65%
“…Variability of the reference genes expression in different tissues and experimental situations was demonstrated in studies of last years [27][28][29][30][31][32]. We also found in the 21 time winners decrease in functional activity of the genes involved in the processes of intracellular protein transport (Cphn) and glycolysis (Gapdh), presented in all nucleated cells (Hprt), which suggests a profound influence of positive fighting experience on different metabolic and cellular processes in the raphe nuclei of the midbrain.…”
Section: Discussionsupporting
confidence: 65%
“…Validation of a normalization protocol is also rare. Times are changing, and several recent reports on the stability of potential reference genes under specific neuropathological conditions are now available (Meldgaard et al, 2006;Rhinn et al, 2008;Santos and Duarte, 2008;Sieber et al, 2008;Valente et al, 2009;Boda et al, 2009;Cook et al, 2009;Gubern et al, 2009). However, to the best of our knowledge, no such study had been published for epilepsy models.…”
Section: Discussionmentioning
confidence: 89%
“…Different solutions exist to determine stable reference genes required for an accurate normalization, such as geNorm (Vandesompele et al, 2002) and NormFinder (Andersen et al, 2004) software, both of which are freely available. They can alleviate the variations in stability of the reference genes that may stem from different experimental conditions and analyzed structures (Derks et al, 2008;Rhinn et al, 2008;Santos and Duarte, 2008;Cook et al, 2009).…”
mentioning
confidence: 99%
“…Such increases in SP immunoreactivity were observed at 5h and shown to persist to at least 24h following trauma in rats [12]. PCR studies later confirmed that SP levels mRNA remained elevated until 3 days post-trauma [46]. Serum levels of SP were also shown to be elevated following trauma, with significant increases observed at 30 mins [12], although levels declined quite rapidly after this time this most likely reflecting the rapid proteolysis of SP within the serum by non-specific proteases.…”
Section: Substance P In Traumatic Brain Injurymentioning
confidence: 85%